Burden and projections of malignant neoplasm of bone and articular cartilage in China: an analysis for the global burden of disease study 2021 - Weiqiang Zeng; Wenlong Yang; Ge Yu; Pan Shen; Zhijun Zheng; Fengyun Yang (BMC Musculoskeletal Disorders)
Abstract Background Malignant neoplasm of bone and articular cartilage (MNBAC) represents one of the most prevalent malignant tumours among adolescents. Assessing its disease burden trends is critical for formulating prevention strategies. This study aims to evaluate the temporal trends of MNBAC burden in China, project future trajectories over the next 15 years, and compare these patterns with global benchmarks. Methods Data on incidence, prevalence, deaths, and disability-adjusted life years (DALYs) were extracted from the Global Burden of Disease (GBD) database 2021. Joinpoint regression analysed temporal trends, while decomposition analysis was used to investigate the impact of aging, population growth, and epidemiological factors on the deaths and DALYs rates of MNBAC. Additionally, we conducted BPAC model to project future trends to 2036. Spearman correlation assessed associations between the burden of MNBAC and the socio-demographic Index (SDI). Results In 2021, China’s age-standardised incidence rate (ASIR), age-standardised prevalence rate (ASPR), age-standardised mortality rate (ASMR) and age-standardised DALYs rate (ASDR) for MNBAC were 1.42, 9.16, 0.93, and 29.52 per 100,000 population, respectively. Compared to 1990, these metrics increased by 118.46%, 125.62%, 60.34%, and 46.43%. Age-specific analyses revealed a bimodal burden pattern globally, peaking in adolescent and elderly populations. Joinpoint regression identified fluctuating trends in China (initial declining, subsequent rise, and then in decline), contrasting with global pattern. Decomposition analysis indicated that the increasing MNBAC burden in China was primarily driven by population aging and epidemiological changes, whereas globally, population growth played a more significant role. Projections indicated modest declines in MNBAC burden for China and globally by 2036. Spearman correlation analysis showed that the ASIR and ASPR of MNBAC in China and globally were significantly positively correlated with SDI (P < 0.05), and the ASMR and ASDR of MNBAC were also positively correlated with SDI, but not significantly. Conclusions This analysis underscores the substantial burden of MNBAC in China, surpassing global trends. While projections suggest gradual declines, the persistent high disability burden in youth and elderly populations necessitates strengthened screening protocols and prevention strategies. These findings provide critical epidemiological evidence for optimizing MNBAC management policies.